An Enhancement of Text Encryption Algorithm with Hybrid Two-Square Cipher and Columnar Transposition Cipher - Ostia, Mary Grace O.; Crisostomo, Alessa L.; Lucas, David Jhozel R.; Atienza, Francis Arlando L.; Dioses, Raymund M.; Guialil, Jamillah S.; Mahusay, Leisyl M.; Morano, Jonathan (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – Enhance the Two-Square Cipher's effectiveness by developing an algorithm to address vulnerabilities in plaintext variations, character set limitations and encryption performance. Method – Proposed adjustments include expanding the grid to 14x14, using table shuﬄing instead of random character insertion, and strategically inserting random special characters in odd-length plaintexts. Results – The algorithm demonstrated improved encryption, producing more random ciphertext sequences and successfully recovering original characters during decryption. Conclusion – The developed algorithm outperforms the current Two-Square Cipher, enhancing encryption security and adaptability to different plaintexts. Recommendations – Further enhance the algorithm to address specific issues such as character transformation, while maintaining the grid size at 14x14. Research Implications – Contributes to advancing cryptographic techniques, highlighting the importance of addressing vulnerabilities in existing ciphers to strengthen data security.